Possibilities of revitalization of unused rural property/Nenaudojamų kaimo statinių atgaivinimo galimybės - Lunkevičius, Sigitas; Ustinovičius, Leonas; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2001)
Unowned and badly managed former kolkhoz property is a national asset of the Republic of Lithuania and it must be protected and effectively used. Problems of rural buildings came to the surface due to unsuccessful reorganization of agricultural sector in Lithuania what has caused the decline of rural property. Part of the rural constructions are still existing and there is a possibility to revitalize and use them, while others have already decayed or are irreversibly decaying and threatening people’s safety, negatively influencing environment, ruining landscape and forming negative public opinion about the authorities’ ability to manage the country. Solution of rural property and its surrounding territory related problem requires exhaustive data. Centralized collection of rural property data was initiated. The collected information is valuable enough, presenting important juridical, technical and market facts, which allow to identify rural property. This respectively treated and generalized information will be used in further scientific research with the aim of making well-founded scientific conclusions, suggestions and recommendations which would create a base for revitalization of rural property. Revitalization of rural property includes modernization, renovation, reconstruction and/or restoration. It covers various processes related to rural property and its improvements. All these processes must be well-founded using investment calculations and evaluations of efficiency investment criteria. Logarithm of revitalization of useless rural property is shown in Fig 8. Revitalization process contains six stages: 1. Adjustment of suitability for use, 2. Research of employment possibilities, 3. Preparation of investment projects, 4. Multicriteria decision-making of investment project, 5. Evaluation of project risk, 6. Realization of investment project. Article in Lithuanian. First Published Online: 30 Jul 2012